Comparison of Bullying and Social Exclusion between Boy and Girl High School Students of Isfahan City - Ziba Karimi; Bahman Kord Tamini (مطالعات روانشناسی تربیتی)
The purpose of the present study was to compare the bullying and social exclusion between boy and girl primary and secondary high school students of Isfahan city in the academic year of 2022 – 2023. The research method was causal – comparative study. The population of this study consisted of all boy and girl primary and secondary high school students of Isfahan city that including 130068 students. The sample size using G Power Software included 316 boy and girl primary and secondary high school students that consisting of 158 boy and 158 girl students which were selected through convenience sampling method. To collect the data Illinois Bullying (2001) and Social Exclusion Questionnaires (Modaresi Yazdi, Farahmand, and Afshani, 2016) were used. The reliability of questioners were .83 for bulling and .79 for social exclusion, respectively. To analyze the data one way MANOVA was used and results revealed that there was a significant difference between boy and girl students on the mean scores of battling sub – scale of bullying and inability sub – scale of social exclusion. Boy students obtained significantly higher mean scores in comparison to girl students (p<.05). But there was not observed any significant differences on the mean scores of the other sub – scales of bullying and social exclusion. Therefore, according to the results of this research, it can be concluded that one of the reasons why boy students engage in physical aggression compared to girl students is their defensive behavior in front of self-protection. It can also be concluded that during adolescence, boy students lack important skills that can reduce loneliness and social isolation, and girl students have effective communication skills, and this issue can reduce social isolation, especially the level of disability in them.